Cybersecurity Challenges in the Modern Banking Industry - Dita Rosyalita (Asian Journal of Multidisciplinary Research, 2026)
The rapid digital transformation of the banking industry has significantly increased the importance of cybersecurity in protecting financial systems and customer information. This study aims to analyze the major cybersecurity challenges faced by modern banking institutions and identify effective strategies to enhance cybersecurity resilience. The research employs a qualitative approach using the library research method by collecting data from academic journals, books, institutional reports, and cybersecurity regulations related to the banking sector. The findings reveal that phishing attacks, ransomware, insider threats, cloud security vulnerabilities, and mobile banking risks are among the most significant cybersecurity challenges in the modern banking industry. Additionally, the study highlights the importance of artificial intelligence, employee awareness, regulatory compliance, and stakeholder collaboration in strengthening banking cybersecurity systems. The research concludes that banks must adopt proactive cybersecurity strategies and continuously improve technological, organizational, and human resource capabilities to maintain customer trust, operational stability, and long-term business sustainability in the digital banking era.